MANAJEMEN PENDIDIKAN AKHLAK BAGI SISWA DI SMA NEGERI 10 BENGKULU - Basinun Basinun (Al-Bahtsu : Jurnal Penelitian Pendidikan Islam, 2017)
Abstract: Moral decline that occurred in the school detected with naughtiness that students do, like smoking, fighting, against teachers and disciplinary breaches. Contributing factor consists of internal factors and external factors. Internal factors such as changes in biological and sociological on students, and external factors, namely the swift currents of globalization with a variety of media and spectacle, the lack of parental supervision and a shift in values in society. Delinquency committed students at SMA Negeri 10 Bengkulu city is still in the category of mild and moderate. It required a specially developed management of the school to improve the quality of student morals. To overcome and reduce student misbehavior create a management school moral education management. Management consists of three phases: planning, implementation phase and evaluation phase. The third stage is applied in three activities, namely the learning activities, extracurricular activities and the activities of habituation.